2000
DOI: 10.2307/1602692
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Home Computer Use on Children's Activities and Development

Abstract: The increasing amount of time children are spending on computers at home and school has raised questions about how the use of computer technology may make a difference in their lives--from helping with homework to causing depression to encouraging violent behavior. This article provides an overview of the limited research on the effects of home computer use on children's physical, cognitive, and social development. Initial research suggests, for example, that access to computers increases the total amount of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
234
1
32

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(277 citation statements)
references
References 31 publications
10
234
1
32
Order By: Relevance
“…We do not attempt to evaluate any of the impacts of computer use, because up to this point, the effects of computer use on children's social development cannot be predicted precisely (e.g. Subrahmanyam et al, 2000). 4.…”
Section: Discussionmentioning
confidence: 99%
“…We do not attempt to evaluate any of the impacts of computer use, because up to this point, the effects of computer use on children's social development cannot be predicted precisely (e.g. Subrahmanyam et al, 2000). 4.…”
Section: Discussionmentioning
confidence: 99%
“…-------------------- Table 7 about here ----------------Having found that access to a computer increases children's total 'screen time', apparently at the expense of other social activities and sports, Subrahmanyam et al (2000) identified a combination of negative and positive effects of computer access, going some way to justify parental anxieties in relation to the domestic regulation of new media. Furthermore, the risks of online communication are becoming increasingly clear (Turow and Ribak, forthcoming;Wolak et al, 2003;Livingstone and Bober, submitted).…”
Section: Providing Media At Homementioning
confidence: 95%
“…The anonymity of the Internet may provide the opportunity to seek information that a child or teenager would be hesitant to ask in person. There is some suggestion that the information obtained online by adolescent girls may actually encourage better sexual decision making (Subrahmanyam et al 2000).…”
Section: Cognitive Developmentmentioning
confidence: 99%